Strategic Trade Policies with Endogenous Mode of Competition - Maggi, Giovanni (American Economic Review, 1996)
This paper develops a model of capacity-price competition in which the equilibrium outcome ranges from the Bertrand to the Cournot outcome as capacity constraints become more important. This model is employed to reexamine aspects of strategic-trade-policy theory and, in particular, the theory's well-known sensitivity to the mode of oligopolistic competition. Among other things, the analysis identifies a simple single-rate policy, namely, capacity subsidies, which can increase the home country's income regardless of the mode of competition. This suggests that the presence of critical informational constraints need not diminish governments' incentives to distort the international competition.